Is the Cis-Element CACCC-Box a Master Regulatory Element during Cardiovascular Disease? A Bioinformatics Approach from the Perspective of the Krüppel-like Family of Transcription Factors - García Loredo, Juan Andrés; Santoyo Suarez, Michelle Giovanna; Rodríguez Núñez, Oscar; Benitez Chao, Diego Francisco; Garza Treviño, Elsa Nancy; Zapata Morin, Patricio Adrián; Padilla Rivas, Gerardo Raymundo; Islas Cisneros, Jose Francisco (2024)
The CACCC-box motif emerges as a pivotal cis-regulatory element implicated in diverse developmental processes and diseases, particularly cardiovascular diseases (CVDs). This study centers on the intricate interplay between the CACCC-box and its binding proteins such as: the Krüppel-Like Family (KLF) of transcription factors as primary effectors in the context of CVDs. Our analysis was through a bioinformatics approach, which revealed significant transcriptional activity among KLF subgroup 2, exhibiting the highest number of interactions focusing on the established roles: pluripotency, cancer, and cardiovascular development and diseases. Our analysis reveals KLF’s interactions with GATA4, MEF2C, NKX2.5 and other ~90 potential genes that participate in the regulation of the hypertrophic environment (or CVDs’ Environment). Also, the GO analysis showed that genes containing the motif CACCC were enriched for multiple CVDs; in combination with STRING analysis, these results pointed to a link between KLFs and these diseases. The analysis further identifies other potential CACCC-box binding factors, such as SP family members, WT1, VEZF1, and -SALL4, which are implicated in cardiac contraction, remodeling, and inflammation processes.